2018
DOI: 10.1111/vco.12404
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of canine osteosarcoma with canine bone marrow stem cells, bone morphogenetic protein and carboplatin in an in vivo model

Abstract: Osteosarcoma (OSA) is the most common malignant bone cancer in children and dogs. The therapeutic protocols adopted for dogs and humans are very similar, involving surgical options such as amputation. Besides surgical options, radiotherapy and chemotherapy also are adopted. However, hematologic, gastrointestinal and renal toxicity may occur because of chemotherapy treatments. Recent study clearly showed that mesenchymal stem cells (MSCs) combined with recombinant human bone morphogenetic protein (rhBMP-2) may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In relation to tumors, in vitro study shows AD-MSCs secrete soluble factors that promote hepatocellular carcinoma cell proliferation and invasion (Teshima, Matsumoto, & Koyama, 2018). dBM-MSCs in combination with recombinant human BMP-2 and cisplatin may act better treatment strategy for canine osteosarcoma (Rici et al, 2018). Further, BM-MSCs and AD-MSCs potential to take up drugs like paclitaxel and then release may help target specific disease conditions like tumors (glioma and glioblastoma; Bonomi et al, 2017) under in vivo conditions, though further studies are required for establishment of the treatment protocol to achieve longer lasting beneficial effects.…”
Section: Miscellaneous Conditionsmentioning
confidence: 99%
“…In relation to tumors, in vitro study shows AD-MSCs secrete soluble factors that promote hepatocellular carcinoma cell proliferation and invasion (Teshima, Matsumoto, & Koyama, 2018). dBM-MSCs in combination with recombinant human BMP-2 and cisplatin may act better treatment strategy for canine osteosarcoma (Rici et al, 2018). Further, BM-MSCs and AD-MSCs potential to take up drugs like paclitaxel and then release may help target specific disease conditions like tumors (glioma and glioblastoma; Bonomi et al, 2017) under in vivo conditions, though further studies are required for establishment of the treatment protocol to achieve longer lasting beneficial effects.…”
Section: Miscellaneous Conditionsmentioning
confidence: 99%
“…By taking advantage of this knowledge, we can load MSCs with therapeutic drugs to exert their anticancer capacity more effectively. It has been reported that rhBMP-2 and MSCs combined with conventional antitumour therapy might be an efficient therapeutic strategy against osteosarcoma [27]. However, conventional chemicals as the carriers in MSCs might disrupt the normal function of MSCs and cause drug delivery failure.…”
Section: Discussionmentioning
confidence: 99%
“…The OS incidence in dogs is ∼27fold higher than in humans, which makes the canine model a more useful model to the human OS for research (Simpson et al, 2017). To date, preclinical research using dogs as animal models has suggested that a combination of canine BMSCs together with rhBMP-2 treatment suppressed OS by increasing p53 and some other pro-apoptotic proteins (Rici et al, 2012(Rici et al, , 2018. However, using dogs as animal models to study the effects of BMP-2 on OS development is not well accepted in Western countries because of social and cultural reasons.…”
Section: Inappropriate Animal Modelsmentioning
confidence: 99%